The Diatom/Dinoflagellate Index as an Indicator of Ecosystem Changes in the Baltic Sea. 2. Historical Data for Use in Determination of Good Environmental Status - Wasmund, Norbert (Frontiers in Marine Science, 2017)
The diatom/dinoflagellate index (Dia/Dino index) serves as an indicator in the assessment of the ecological status of the Baltic Sea within the scope of the Marine Strategy Framework Directive. It describes the dominance patterns in the phytoplankton spring bloom. Implementation of this indicator requires a definition of the conditions describing good environmental status (GES). The aim of this study was to determine thresholds for GES for the Dia/Dino index on the basis of historical phytoplankton data from different regions of the Baltic Sea. Data from the first half of the 20th century, corresponding to the pre-eutrophication period, provide an unadulterated reference, as exemplified by nutrient data. Early phytoplankton data showed high dominance of diatoms over dinoflagellates in spring blooms. Diatom dominance relates to a Dia/Dino index > 0.5, which allowed GES threshold of the Eastern Gotland Basin to be set at a Dia/Dino index of 0.5. The consistently very high Dia/Dino index in Kiel and Mecklenburg Bays supported a previously suggested GES threshold value of 0.75. Recent monitoring data revealed a sudden decrease of the Dia/Dino index, especially between 1984 and 1991, and thus a worsening environmental status. This deterioration could be attributed to warming rather than to eutrophication.